Altered Amygdala Excitation and CB1 Receptor Modulation of Aggressive Behavior in the Neuroligin-3R451C Mouse Model of Autism - Hosie, Suzanne; Malone, Daniel T.; Liu, Stephanie; Glass, Michelle; Adlard, Paul Anthony; Hannan, Anthony John; Hill-Yardin, Elisa L. (Frontiers in Cellular Neuroscience, 2018)
Understanding neuronal mechanisms underlying aggression in patients with autism spectrum disorder (ASD) could lead to better treatments and prognosis. The NL3R451C mouse model of ASD, has a heightened aggressive phenotype, however the biological mechanisms underlying this behaviour are unknown. It is well established that NL3R451C mice have imbalanced excitatory and inhibitory synaptic activity in the hippocampus and somatosensory cortex. The amygdala plays a major role in modulating aggressive behaviour, however potential changes in synaptic activity in this region have not previously been assessed in this model. We investigated whether aggressive behaviour is robustly present in mice expressing the R451C mutation, following back-crossing onto a congenic background strain. Endocannabinoids influence social interaction and aggressive behaviour, therefore we also studied the effects of cannabinoid receptor 1 (CB1) agonist on NL3R451C mice. We report that NL3R451C mice have increased amplitude of miniature excitatory postsynaptic currents (EPSCs) with a concomitant decrease in the amplitude of inhibitory postsynaptic currents (IPSCs) in the basolateral amygdala. Importantly, we demonstrated that NL3R451C mice bred on a C57Bl/6 background strain exhibit an aggressive phenotype. Following non-sedating doses (0.3 and 1.0 mg/kg) of the CB1 receptor agonist WIN55,212-2 (WIN), we observed a significant reduction in aggressive behaviour in NL3R451C mice. These findings demonstrate altered synaptic activity in the basolateral amygdala and suggest that the NL3R451C mouse model is a useful preclinical tool to understand the role of CB1 receptor function in aggressive behaviour. Furthermore, this data supports the CB1 receptor as a promising target for new therapeutic approaches to treat aggression.